(untitled) (Journal of Nobel Medical College, 2020)
Background: Sciatic nerve, the thickest nerve of our body (around 2cm wide at its origin), leaves the pelvic cavity from the greater sciatic foramina below the piriformis muscle and between the greater trochanter of femur and ischial tuberosity. As variations have been reported in the level of division of sciatic nerve into its terminal branches, the current study aims to determine the most common site of division of sciatic nerve in Nepalese population. Materials and Methods: The current study is a cross-sectional and descriptive study which was carried out in the Department of Anatomy, Nobel Medical College, where twenty-three cadavers were used and both the lower limbs were examined. Depending upon the level of division of the sciatic nerve into its terminal branches, it was categorized into six different groups (A-F). Results: It was seen that the sciatic nerve had already divided into its terminal branches before its exit into the gluteal regionin 23.91% extremities. The second commonestsite for the termination of sciatic nerve into its terminal branch was found to be at the middle region of the back of the thigh in 19.57% followed by its division in the popliteal fossa in 17.39%. Conclusion: From the current study we conclude that the level of division of sciatic nerve was variable and it is wise to go for other means to find out the level of termination of sciatic nerve before performing any procedure in that area.